PENGARUH CITRA MEREK DAN HARGA TERHADAP TINGKAT HUNIAN KAMAR DI ARYADUTA HOTEL MANADO - Sony Wijanarko; Novianty Zalvena Weku (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
This study aims to find out how the Influence of Brand Image and Price on Room Occupancy Rate at Aryaduta Hotel Manado. The method used in this study is the Quantitative Method, with the Multiple Linear Regression data analysis technique. Thepopulation in this study is Hotel Guests, with a sample of 60 Guests at Aryaduta Hotel Manado. The results of this study prove that Brand Image has a positive and significant effect on the Room Occupancy Rate with a regression coefficient value of 0.376 and asignificance of 0.000. This shows that if the value of the Brand Image increases, the Room Occupancy Rate will also increase. Price has a significant positive effect on the Room Occupancy Rate with a regression coefficient value of 0.759 and a significance of 0.000.This shows that the better the price offered at the hotel, the higher the Room Occupancy Rate. Brand Image and Price have a significant influence on the Room Occupancy Rate with an F value of 388.375 and a significance of 0.000. This shows that the better theBrand Image and Price, the more the Room Occupancy Rate will also increase. The conclusion of this study is that Brand Image and Price simultaneously have a significant effect on the Room Occupancy Rate at Aryaduta Hotel Manado. The advice given is that Aryaduta Hotel Manado must provide quality service and the price offered is in accordance with the Quality and Image of the Hotel to increase the Room Occupancy Rate at Aryaduta Hotel Manado.